(untitled) (Praxis Educativa, 2024)
Universities are a formative scenario that transforms reality and their actions must go beyond commitment and citizen solidarity. The objective of this review article is to present a study on the conceptualization, definition and education in values, and an analysis of the theoretical-methodological referents of University Social Responsibility. Systematic literature review and bibliometric analyses were carried out in the programs VOSviewer version 1.6.19 and Connected Papers. The results show that strengthening the sense of identity and belonging of the competent professional committed to academic, economic, social and environmental actions, with respect to the place where he/she studies, lives and works, is fundamental to achieve transformations in order to improve the quality of citizenship education. In conclusion, it is necessary to continue stimulating the apprehension of the value of university social responsibility in higher education institutions.